Implementers? The role of international organisations in EU funding for external migration policy - Den Hertog Leonhard (Journal of Regional Security, 2017)
The EU is a major funder of migration projects around the world. There is a relationship of interdependence between the EU and international organizations, with the former offering funding and the latter offering implementation capacity. This paper explores this relationship in more detail. In particular, it explores how these international organizations are involved in the EU funds beyond implementation. This paper employs an organization theory approach to explain this central role of international organizations. This article argues that these organizations carefully navigate between the 'company' and 'political' organizational types. Moreover, the Commission and these organizations can be better conceptualized as forming a 'partial' organization. This holds implications for transparency and accountability in this area of growing spending. Three organizations are looked at in the context of this paper: The International Organization for Migration (IOM), the UN High Commissioner for Refugees (UNHCR), and the International Centre for Migration Policy Development (ICMPD).